2017
DOI: 10.1177/0263092317714697
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation and experimental research on the aerodynamic performance of large marine axial flow fan with a perforated blade

Abstract: In this study, some of the optimal parameters for a new-style marine axial flow fan are defined by using numerical simulation and experimental tests with a large marine axial flow fan, based on the analysis of the blade perforation’s influences on its internal flow field and aerodynamic noise characteristics. Test result shows that the noise reduction for the axial flow fan with perforated blade is about 3 dB when the blade perforation diameter D is 10 mm and its deflection angle α is 45°. The results of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The monitoring of complex inner flow phenomena in the hydraulic machinery has been a hot topic. 5,6 The detection and diagnosis of the inception and the severity of cavitation provide means for preventing accidents. When severe cavitation occurs, it is usually accompanied by significant noise.…”
Section: Introductionmentioning
confidence: 99%
“…The monitoring of complex inner flow phenomena in the hydraulic machinery has been a hot topic. 5,6 The detection and diagnosis of the inception and the severity of cavitation provide means for preventing accidents. When severe cavitation occurs, it is usually accompanied by significant noise.…”
Section: Introductionmentioning
confidence: 99%
“…If there is only one impeller and there is no a directing vane, the aerodynamic imbalance and noise of the fan are determined mainly by the aerodynamic characteristics of blades. Papers [9][10][11][12][13] investigated and optimized separate blades. Authors of [9] studied the impact of through openings in a blade on the noise of the fan.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Axial fans are widely used in industry and in everyday life [1][2]. Reduction of noise and vibration during operation of axial fans is a relevant scientific and technical task [3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Ordinary and aerodynamic (gas-dynamic) imbalances of the fan impellers are the main source of vibrations in fan machines [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their results indicated that the convex grooves on the blade pressure surface changed the turbulent structures near the wall, and the wave-shaped trailing edge changed the flow direction of vortex shedding, which would reduce the influence of vortex shedding on the far-field region. Yang et al [7] analyzed the influence of the blade perforation on the internal flow field and aerodynamic noise characteristics. The results showed that the perforated blades improved the flow in the axial fan and reduced the pressure pulsation amplitude caused by the turbulence of the blade surface boundary layer.…”
Section: Introductionmentioning
confidence: 99%